RANCANGAN SISTEM INFORMASI DATA NASABAH PADA ASURANSI BERINGIN LIFE JAMBI - Mulyadi - (JURNAL AKADEMIKA)
One effort to create the efficiency of the insurance company in order to prepare a draft agreement draft- insurance policies hearts , hearts printed Forms and Contracts OR make raw Become agreement . In the situation created Contracts hearts printed circumstances and attempted hearts Posted raw Form Insurance Company. Banyan Life Insurance HAVE using computer tools , because so much data Accident Yang processed , then the Banyan Life Insurance In data processing still using manual systems , where data processing is still using the calculator so that TO processing data that was so effective and efficient yet , BECAUSE so There was delay in informing its data hearts . Then the author will design a new System State WITH enhance long Systems , Banyan Life Insurance pada WITH using Visual Basic 6.0 programming package .